2021
DOI: 10.1159/000515125
|View full text |Cite
|
Sign up to set email alerts
|

The Increased Trend of Medical Treatment for Thyroid Diseases during Pregnancy: A 13-Year National Study

Abstract: <b><i>Objective:</i></b> Thyroid dysfunction affects up to 5–7% of all pregnancies. The rates of thyroid hormone use in nonpregnant population have substantially increased in recent years. The aim of this study was to assess possible changes in the use of levothyroxine substitution and antithyroid drugs over time in pregnant women. <b><i>Methods:</i></b> The study data consisted of all singleton pregnancies (<i>N</i> = 736,873) between 2004 and 2016 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
2
5
1
Order By: Relevance
“…Our results are very much comparable to the recent similar study in Finland which found a five-fold increase in levothyroxine use among pregnant women from 1.1% in 2004 to 6.2% in 2016 (14). We found a smaller increase in the Norwegian numbers (2.4-fold); however, the proportion of women using thyroid hormone replacement therapy was lower (3.57% in 2018).…”
Section: Discussionsupporting
confidence: 88%
“…Our results are very much comparable to the recent similar study in Finland which found a five-fold increase in levothyroxine use among pregnant women from 1.1% in 2004 to 6.2% in 2016 (14). We found a smaller increase in the Norwegian numbers (2.4-fold); however, the proportion of women using thyroid hormone replacement therapy was lower (3.57% in 2018).…”
Section: Discussionsupporting
confidence: 88%
“…Studies from other countries of trimester‐specific medication use also reported anti‐infectives to be the most commonly prescribed medication in the first trimester, including in Canada, Norway, Sweden, and Denmark 31–36 . In concordance with our findings, use of anti‐infectives, NVP, anti‐depression/anxiety, fertility, anti‐diabetic and thyroid medications appear to be increasing outside of the United States 24,33,37–41 . However, demographic patterns of medication use among pregnant women in other countries differed from those presented here, owing to variations in prescribing patterns of specific products 27 …”
Section: Discussionsupporting
confidence: 85%
“…[31][32][33][34][35][36] In concordance with our findings, use of antiinfectives, NVP, anti-depression/anxiety, fertility, anti-diabetic and thyroid medications appear to be increasing outside of the United States. 24,33,[37][38][39][40][41] However, demographic patterns of medication use among pregnant women in other countries differed from those presented here, owing to variations in prescribing patterns of specific products. 27 In conclusion, we found that prescription medication use in the first trimester of pregnancy is common and increasing.…”
Section: Articlecontrasting
confidence: 73%
“…The variations in our trimester-specific reference ranges, alongside disparities noted in published data from international studies, prompt questioning the accuracy of thyroid function test interpretation in pregnant women. Following fixed reference ranges often results in unnecessary or untimely treatment, posing risks of both delayed diagnosis and treatment and overdiagnosis, which can lead to complications during pregnancy [9,[35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%